Government `schedule of rates': working against rural labour - Vijay Shankar, P.S. et al. (2006)
The schedule of rates that state governments currently use to value work done by labour employed in schemes needs to be substantially revised if the promise of the National Rural Employment Guarantee Scheme is to be realised. The schedules now have an inherent pro-contractor bias, encourage the use of machinery and make it virtually impossible for labourers to earn minimum wages. - Reproduced.
Keywords: Employment; Wages; Labour; Minimum wage